Cultural Commodification in Indian and Turkish Films on ANTV - Isnawijayani, Isnawijayani; Zinaida, Rahma Santhi; P.L, Siti Rahayu; Triwidayatsih, Triwidayatsih; Taqwa, Dwi Muhammad; Wedadjati, Ratna Sesotya (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
Competition in the television industry allows a company to take long steps forward in a society saturated with the current situation. Various studies show that ANTV's strategy to buy many programs in Indian drama series in Indonesia has been exceeded; the India program screening strategy at ANTV itself is a form of adaptation of ANTV's strategy in dealing with the convergence and growth of the industry, especially the internet. This study uses qualitative methods with media political-economic theory specific to commodifying content. The primary data was obtained through observation, and secondary data were obtained through interviews. As a result, the commodification of the content carried out by ANTV TV stations was by displaying Indian program content that was very much in percentage so that it indoctrinated the audience to overindulge India & Türkiye culture from films, actresses, arts and culture finally eroded local culture due to the many hours of India &Türkiye import program broadcast on ANTV.